2018
DOI: 10.1111/jace.16141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of (Zr1/3Nb1/3Ti1/3)C metal carbide solid‐solution ceramic

Abstract: (Zr1/3Nb1/3Ti1/3)C metal carbide solid‐solution ceramic has been successfully fabricated by hot pressing sintering at 2473 K using ZrC, NbC, and TiC powders as raw materials. The results show that the as‐prepared solid‐solution ceramic possesses a single rock‐salt crystal structure of metal carbides and simultaneously exhibits high compositional uniformity from nanoscale to microscale. By taking advantage of these unique features, it shows relatively high hardness of 38.8 ± 4.4 Gpa and elastic modulus of 481.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 30 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the interatomic bonding of TZHC is relatively strong, which results in an increase in flexural strength. Similar solid solution strengthening mechanisms can be found in (Hf,Ta)C, 21 (Zr,Nb,Ti)C, 10 and (Ta,Zr,Nb) C 16 solid solutions. TZHC ceramics not only have higher flexural strength at 25°C-1800°C, but also good phase stability.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, the interatomic bonding of TZHC is relatively strong, which results in an increase in flexural strength. Similar solid solution strengthening mechanisms can be found in (Hf,Ta)C, 21 (Zr,Nb,Ti)C, 10 and (Ta,Zr,Nb) C 16 solid solutions. TZHC ceramics not only have higher flexural strength at 25°C-1800°C, but also good phase stability.…”
Section: Resultssupporting
confidence: 74%
“…In most studies, multicomponent carbide solid-solution ceramics exhibit excellent mechanical properties. Ye et al 10 used ZrC, NbC, and TiC powders as raw materials to synthesize (Zr,Nb,Ti)C metal carbide solid-solution ceramics, and the obtained ceramic has relatively high hardness and elastic modulus, which may be attributed to the presence of solid solution effects. Gorbanet et al 11 prepared coatings of high-entropic carbide based on a (Ti,Zr,Hf,V,Nb,Ta)C multicomponent alloy, and the obtained coatings exhibited higher hardness than the individual carbides of metals that entered the composition of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al employed monocarbides as original materials to synthesize high-entropy carbide powders with better oxidation resistance than the corresponding monocarbides at 1400 • C. 16 Lu et al reported that the addition of SiC to (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )C not only inhibited the grain growth during sintering but also accelerated the densification process. 8 Research on the mechanical properties of carbide ceramics is limited to their Young's modulus, 3,17 hardness, 2 fracture toughness 18 at room temperature, and high-temperature creep resistance. 19 However, the high-temperature strength has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Among the existing solid-solution ceramics, the solid-solution ceramics of transition-metal carbides, are regarded as the most ideal candidates for the extreme environment since their individual metal carbide components possess high melting point (>3000°C), outstanding high-temperature stability, and good mechanical performance. [7][8][9] Up to now, numerous methods have been developed to synthesize the solid-solution ceramics of transition-metal carbides, including reaction sintering, 7,10 carbothermal reaction, 11,12 arc melting, 13 and polymer-derived-ceramic (PDC) route. 14,15 Among those advanced fabrication methods, PDC route is considered as an ideal route to obtain ceramic matrix composites due to its advantage of polymer-processing techniques.…”
Section: Introductionmentioning
confidence: 99%